#TITLE_ALTERNATIVE# - Rozieanshah (NIM 132 03 054), Rhobi
Abstract: This final project describes the use of wavelet transform for analyzing power system fault transients in order to determine the fault type and its location at high voltage transmission line. This method is applying travelling wave theory to determine the travel time of transient wave alongside transmission line between fault point and sending end. Measurement is done at one point, that is at sending end. The fault signal, in the form of voltage signal, is converted into two mode by using Clarke transform. Those are ground mode and aerial mode. Ground mode is used to identify fault type that occurred (ungrounded/symmetrical fault or grounded fault). Whereas aerial mode is used for determining fault location. Wavelet transform is used to calculating time differential between arrival time of first reflectected wave peak and arrival time of second reflected wave peak at aerial mode. For ground mode, wavelet transform is applied to getting wavelet transform coefficient value, that later is used to identify the type of fault. ATP software is considered to implement fault simulation. MATLAB 7.3 version is used for signal processing. Simulation is done for various sampling frequency, fault type, voltage phase angle, and fault location. Simulation results is shown that this method can determine the fault type and location with high level accuration.